Separation and Identification of Phenolic Acid from Borago officinalis (F:Boraginaceae) Cultivated in Iraq - Kareem, Ashwaq T; N. Hamad, Maha (Iraqi Journal of Pharmaceutical Sciences, 2020)
The plant Borago officinalis, which belongs to the Boraginaceae family and Celebrated as borage, is one of the useful medicinal plants cultivated in Iraq. It was used in olde medicine in Iraq, Irane, Syria and Europe for management of various diseases. It is commonly used as an atonic, tranquilliser, management of cough, sore throat, pneumonia, swelling, inflammatory diseases, antioxidant, and anticancer. This project provides the first comprehensive research done in Iraq to study the phytochemicals and the methods of extraction and isolation of active constituents from Borago officinalis cultivated in Iraq. The plant was harvested in spring from AL-Rifai, Nassiriyah city, IRAQ in February 2019.were washed carefully, dried under dark, and milled in a mechanical grinder to a fine powdere then measure the weight of the plant.The plant was extracted by cold extraction methods using (85%absolute methanol ) solvent for three days then Fractionation was done by petrollium ethere, chloroform, ethyl acetate and n-butanol(n.b) to separate the active constituentse according to the change in polaritiese. The phytochemical screening exposed the presence of, phenols, tannins, fatty acid, in the plant’s Ethyl acetate fraction, n-butanol fraction was usedfor identification and isolationof phenolic compoundsby by TLC, PLC HPLC andLC/mass. The Phenolic acid (Sinapic acide, Rosmarinic acides,Caffeic acid) were seperated and purified by PLC. The isolated compounds were subjected to several chemical chromatographic and spectral analytical techniques for their identification, such as TLC, PLC, HPLC, UV, and LC/mass.